Modelling the Structure and Dynamics of Biological Pathways. - Laura O'Hara; Alessandra Livigni; Thanos Theo; Benjamin Boyer; Tim Angus; Derek Wright; Sz-Hau Chen; Sobia Raza; Mark W Barnett; Paul Digard; Lee B Smith; Tom C Freeman (PLoS Biology)
There is a need for formalised diagrams that both summarise current biological pathway knowledge and support modelling approaches that explain and predict their behaviour. Here, we present a new, freely available modelling framework that includes a biologist-friendly pathway modelling language (mEPN), a simple but sophisticated method to support model parameterisation using available biological information; a stochastic flow algorithm that simulates the dynamics of pathway activity; and a 3-D visualisation engine that aids understanding of the complexities of a system's dynamics. We present example pathway models that illustrate of the power of approach to depict a diverse range of systems.